Pulling Back from the Brink: Fiscal Decentralization and Political Stability in China, 1979-1993 - Chua, Ciqi Annabel (Tufts Archival Research Center, 2005)
In the post-Mao era, China underwent a series of fiscal decentralization reforms from 1979 to 1993. Many scholars have predicted that these reforms would have destabilized China during this period. These scholars were informed by the collapse of the former Soviet Union following the introduction of similar fiscal decentralization reforms. However, China was able to pull back from the brink of political instability to remain politically stable. Why was China able to remain politically stable in the aftermath of the fiscal decentralization reforms and did the fiscal decentralization reforms contribute to the political stability of China from 1979 to 1993? There has been no direct, extensive analysis of the relationship between fiscal decentralization and social stability in China or the legitimacy of the Chinese Communist Party (CCP) during this period. My thesis addresses this gap in the literature by testing two hypotheses: (i) fiscal decentralization strengthened social stability through increasing government expenditure on social control instruments such as the media and the People's Armed Police Force (PAP); and (ii) fiscal decentralization strengthened the legitimacy of the CCP through promoting economic growth and creating a political buy-in effect. My findings indicate that both hypotheses are disconfirmed. Fiscal decentralization did not enable China to pull back from the brink of political instability from 1979 to 1993.